Preparation method and application of injectable nano composite hydrogel for relieving osteoarthritis

Osteoarthritis was solved by preparing nanocomposite hydrogels containing hydrophilic hydroxyapatite of strontium and europium ions, chondroitin sulfate of grafted hydrazide groups and oxidized hyaluronic acid of grafted benzene boric acid groups. The complex therapeutic needs of the treatment achieve subchondral bone repair and inflammatory regulation, providing an efficient and biocompatible treatment plan.

CN119258007AActive Publication Date: 2025-01-07NORTHWEST UNIV

Patent Information

Application Number
CN202411283370.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-07
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The prior art cannot effectively alleviate osteoarthritis, especially in the inflammatory response in the organisms and the activity and toxicity of materials, and it is difficult to meet the complex treatment needs of osteoarthritis, especially for subchondral bone repair and local immune regulation. aspect.

Method used

Prepare an injectable nanocomposite hydrogel, by doping hydrophilic hydroxyapatite with strontium and europium ions, chondroitin sulfate of grafted hydrazide groups, oxidized hyaluronic acid with grafted benzene boric acid groups and The combination of recombinant collagen forms nanocomplexes with good biocompatible to relieve osteoarthritis and promote subchondral bone repair.

Benefits of technology

This nanocomposite hydrogel can create a favorable local immune microenvironment, regulate macrophages, reduce high reactive oxygen levels, promote chondrocyte proliferation and bone repair, reduce inflammatory response, and has good biocompatibility and market application value .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258007A_ABST
    Figure CN119258007A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of injectable nano composite hydrogel for relieving osteoarthritis, which comprises the following steps: firstly, synthesizing nano rod-like hydroxyapatite with the length of 150-300 nm and the diameter of 10-15 nm, and the hydroxyapatite is hydrophilic hydroxyapatite doped with strontium and europium ions; the preparation method comprises the following steps: by taking Ca (NO3) 2, Sr (NO3) 2, Eu (NO3) 3 and soluble phosphate as main raw materials, carrying out hydrothermal reaction to prepare strontium and europium ion co-doped hydrophobic hydroxyapatite, dispersing the strontium and europium ion co-doped hydrophobic hydroxyapatite in a Tris-HCl buffer solution, adding tannic acid, stirring, centrifugally collecting precipitate, and drying to obtain strontium and europium ion doped hydrophilic hydroxyapatite; the preparation method comprises the following steps: taking chondroitin sulfate and adipic dihydrazide as main raw materials, stirring, dialyzing, freeze-drying, and dissolving in a buffer solution to obtain the chondroitin sulfate solution grafted with the hydrazide group; the preparation method comprises the following steps: taking hyaluronic acid, 3-aminophenylboronic acid and sodium periodate as main raw materials, stirring, dialyzing, freeze-drying, and dissolving in a buffer solution to obtain the phenylboronic acid group grafted oxidized hyaluronic acid solution; the preparation method comprises the following steps: blending hydrophilic hydroxyapatite doped with strontium and europium ions, a chondroitin sulfate solution grafted with a hydrazide group, an oxidized hyaluronic acid solution grafted with a phenylboronic acid group and a recombinant collagen solution, and stirring to obtain the injectable nano composite hydrogel. The injectable nano composite hydrogel obtained by the invention has good biocompatibility, and a favorable local immune microenvironment can be created to immunomodulate macrophages so as to relieve osteoarthritis and promote subchondral bone repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of an injectable nano composite hydrogel for relieving osteoarthritis, belonging to the technical field of biomaterials. Background Art

[0002] Articular cartilage is a supporting connective tissue characterized by toughness, viscoelasticity and lubrication. It is essential for load bearing and joint lubrication during joint movement. Osteoarthritis, characterized by cartilage degeneration and subchondral bone remodeling, affects more than 7% of the world's population. The knee joint is the most commonly affected joint, with 365 million people suffering from the disease, followed by the hand joints and hip joints. With the acceleration of aging and the increase in obesity rates in my country, the number of osteoarthritis patients will continue to increase. The pathological characteristics of osteoarthritis are mainly high reactive oxygen levels, macrophage M 1 / M 2 There are four aspects: phenotypic imbalance, bone defects, and synovial fluid damage. The current treatment measures still cannot fully meet the complex needs of osteoarthritis treatment. At the same time, for organisms, the activity and toxicity of materials, how to reduce the inflammatory response of implants, and how to meet the irregular morphology of inflammatory sites have always been issues that cannot be ignored. Therefore, it is crucial to construct an injectable nanocomposite hydrogel with good biocompatibility, the ability to reduce reactive oxygen levels, reprogram macrophage polarization, promote osteogenesis, and lubricate to relieve osteoarthritis. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a preparation method of an injectable nanocomposite hydrogel for relieving osteoarthritis in view of the deficiencies of the prior art. The injectable nanocomposite hydrogel obtained by the present invention has good biocompatibility and can create a favorable local immune microenvironment to immunoregulate macrophages, thereby relieving osteoarthritis and promoting subchondral bone repair.

[0004] The implementation process of the present invention is as follows: A method for preparing an injectable nanocomposite hydrogel for relieving osteoarthritis comprises the following steps: (1) Preparation of hydrophilic hydroxyapatite doped with strontium and europium ions, specifically comprising: 3 ) 2 、Sr(NO 3 ) 2 、Eu(NO 3 ) 3The aqueous solution of phosphate and the aqueous solution of soluble phosphate are successively dissolved in the methanol solution of methyl oleate to obtain a mixed solution, the mixed solution is reacted in a closed reactor at 100-200°C for 5-15 hours, and the precipitate is collected; the precipitate is dispersed in Tris-HCl buffer, tannic acid is added, the mixture is stirred thoroughly, and the precipitate is collected to obtain hydrophilic hydroxyapatite doped with strontium and europium ions with a length of 150-300 nm and a diameter of 10-15 nm; (2) preparing a solution of chondroitin sulfate grafted with hydrazide groups, specifically comprising: dissolving 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide in an aqueous solution of chondroitin sulfate at a pH of 5 to 6 and stirring the solution to activate the carboxyl groups; adding adipic acid dihydrazide to the system after the carboxyl groups are activated for a sufficient reaction; transferring the system after the reaction to dialysis and freeze-drying to obtain chondroitin sulfate grafted with hydrazide groups; dissolving the chondroitin sulfate grafted with hydrazide groups in a PBS buffer solution to obtain a solution of chondroitin sulfate containing grafted hydrazide groups; (3) preparing a hyaluronic acid solution grafted with phenylboronic acid groups, specifically comprising: placing 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide in an aqueous solution of hyaluronic acid at a pH of 5 to 6 and stirring thoroughly to activate the carboxyl groups; adding 3-aminophenylboronic acid to the system after the carboxyl groups are activated to react thoroughly; transferring the system after the reaction to dialysis, and freeze-drying to obtain hyaluronic acid grafted with phenylboronic acid groups; dissolving the oxidized hyaluronic acid grafted with phenylboronic acid groups in deionized water to obtain an aqueous solution of hyaluronic acid containing grafted with phenylboronic acid groups; (4) preparing an oxidized hyaluronic acid solution grafted with phenylboronic acid groups, specifically comprising: dissolving sodium periodate in an aqueous solution of hyaluronic acid grafted with phenylboronic acid groups, adding ethylene glycol after sufficient reaction in a dark environment, and stirring to terminate the reaction; dialyzing the system after the termination of the reaction, and freeze-drying to obtain an oxidized hyaluronic acid grafted with phenylboronic acid groups; dissolving the oxidized hyaluronic acid grafted with phenylboronic acid groups in a PBS buffer solution to obtain an oxidized hyaluronic acid solution containing grafted with phenylboronic acid groups; (5) Preparing an injectable nanocomposite hydrogel, specifically comprising: uniformly blending the hydrophilic hydroxyapatite doped with strontium and europium ions in step (1), the chondroitin sulfate solution grafted with hydrazide groups in step (2), the oxidized hyaluronic acid solution grafted with phenylboronic acid groups in step (4), and the recombinant collagen solution to obtain the injectable nanocomposite hydrogel.

[0005] The preparation method of the injectable nanocomposite hydrogel for relieving osteoarthritis, in step (1), in the methanol solution of methyl oleate, the volume of methanol is 3 to 7 times the volume of methyl oleate; the molar ratio of (Ca+Sr+Eu) / P is 1.67, and the molar ratio of Sr / (Ca+Sr+Eu) is 0.05 to 0.5; the soluble phosphate is selected from Na2 HPO 4 、Na 3 PO 4 12H 2 O、NaH 2 PO4, KH 2 PO 4 or K 2 HPO 4 ; The molar ratio of Eu / (Ca+Sr+Eu) is 0.05~0.5; the volume of the cyclohexane is 10~100 times the mass of the precipitate, the unit of the cyclohexane volume is mL, and the unit of the precipitate mass is g; the mass of the tannic acid is 3~6 times the mass of the precipitate.

[0006] In the method for preparing the injectable nanocomposite hydrogel for relieving osteoarthritis, in step (2), the mass of the 1-ethyl-(3-dimethylaminopropyl)carbodiimide is 1 to 2 times the mass of chondroitin sulfate, the mass of the N-hydroxysuccinimide is 1 to 2 times the mass of chondroitin sulfate; and the mass of the adipic acid dihydrazide is 0.67 to 2 times the mass of chondroitin sulfate.

[0007] In the method for preparing the injectable nanocomposite hydrogel for relieving osteoarthritis, in step (3), the mass of the 1-ethyl-(3-dimethylaminopropyl)carbodiimide is 1 to 2 times the mass of hyaluronic acid, the mass of the N-hydroxysuccinimide is 1 to 2 times the mass of hyaluronic acid, and the mass of the 3-aminophenylboronic acid is 0.2 to 1 times the mass of hyaluronic acid.

[0008] In the method for preparing the injectable nanocomposite hydrogel for relieving osteoarthritis, in step (4), the mass of the sodium periodate is 1 to 3 times the mass of the hyaluronic acid grafted with phenylboronic acid groups; the volume of the ethylene glycol is 1.25 to 6.25 times the mass of the hyaluronic acid grafted with phenylboronic acid groups, the volume unit of the ethylene glycol is mL, and the mass unit of the chondroitin sulfate is g.

[0009] In the method for preparing the injectable nanocomposite hydrogel for relieving osteoarthritis, in step (5), the concentration of the hydrophilic hydroxyapatite doped with strontium and europium ions is 0.05-1 g / mL, the concentration of the chondroitin sulfate solution grafted with hydrazide groups is 5-50%, the concentration of the oxidized hyaluronic acid solution grafted with phenylboronic acid groups is 5-50%, and the concentration of the recombinant collagen solution is 5-50%; the volume ratio of the chondroitin sulfate solution grafted with hydrazide groups, the oxidized hyaluronic acid solution grafted with phenylboronic acid groups, and the recombinant collagen solution is (1-5):(1-10):(1-5).

[0010] The injectable nanocomposite hydrogel prepared by the above method is used in the preparation of medicines for treating and relieving osteoarthritis.

[0011] Compared with the prior art, the present invention has the following advantages: 1. The hydrophilic hydroxyapatite doped with strontium and europium ions in the injectable nanocomposite hydrogel of the present invention is in the shape of nanorods with a length of 150-300 nm and a diameter of 10-15 nm. The strontium ions have the ability to promote chondrocyte proliferation, and the europium ions have the ability to promote macrophage M 1 Type M 2 Type polarization, thereby alleviating inflammation; 2. The chondroitin sulfate, hyaluronic acid and recombinant collagen in the injectable nanocomposite hydrogel of the present invention are all natural cartilage components, have good biocompatibility, and can simulate the extracellular matrix environment of cartilage cells to play a lubricating role; 3. The hydrophilic hydroxyapatite doped with strontium and europium ions in the injectable nanocomposite hydrogel of the present invention is bonded to the oxidized hyaluronic acid grafted with phenylboronic acid groups through a borate bond. The borate bond is a chemical bond that breaks at high reactive oxygen levels. When it infiltrates into the microenvironment of osteoarthritis with high reactive oxygen levels, it breaks, thereby uniformly dispersing the hydrophilic hydroxyapatite doped with strontium and europium ions in the hydrogel and achieving responsive release. 4. The injectable nanocomposite hydrogel of the present invention can be implanted into the osteoarthritis site in a non-invasive or minimally invasive manner, which can create a favorable local immune microenvironment to immunomodulate macrophages to alleviate osteoarthritis and promote subchondral bone repair, while avoiding damage to surrounding normal tissues; 5. The preparation method of the injectable nanocomposite hydrogel of the present invention is simple, the raw materials are cheap and easily available, the process is environmentally friendly, it is easy to scale up, and it has good market application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 is a TEM image of the hydrophilic hydroxyapatite doped with strontium and europium ions of Example 1; Figure 2 is the XRD pattern of the hydrophilic hydroxyapatite doped with strontium and europium ions of Example 1; Figure 3 FT-IR images of the Sr and Eu co-doped hydroxyapatite before and after hydrophilic modification in Example 1; Figure 4 FT-IR images of chondroitin sulfate before and after modification in Example 4; Figure 5 1H-NMR diagram of chondroitin sulfate before and after modification in Example 4; Figure 6 FT-IR images of hyaluronic acid before and after modification in Example 7; Figure 7 1H-NMR diagram of hyaluronic acid before and after modification in Example 7; Figure 8 A schematic diagram of the injectable performance of the injectable hydrogel described in Example 10; Fig. 9 Schematic diagram of the experimental results of the efficacy of the injectable hydrogel on chondrocytes in Example 10. DETAILED DESCRIPTION

[0013] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials and reagents used, unless otherwise specified, can be obtained from commercial sources. The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Example 1

[0014] This embodiment provides a hydrophilic hydroxyapatite doped with strontium and europium ions, and the preparation method thereof includes: (1) Under magnetic stirring, 1 mL of methyl oleate and 3 mL of methanol were mixed to obtain a precursor solution; 5.6 mL of 0.28 M Ca(NO 3 ) 2 of aqueous solution, 0.7 mL of 0.28 M Sr(NO 3 ) 2 of aqueous solution and 0.7 mL of 0.28 M Eu(NO 3 ) 3 The aqueous solution was stirred for 10 min and 7 mL of 0.168 M Na 3 PO 4 The aqueous solution was stirred for 10 minutes to obtain a mixed solution A; the mixed solution A was placed in a polytetrafluoroethylene reactor, sealed, and reacted at 130° C. for 10 hours; the system after the reaction was cooled to room temperature, and the precipitate was collected by centrifugation; (2) Disperse 0.05 g of the precipitate in 100 mL of Tris-HCl buffer, add 0.15 g of tannic acid, stir for 4 h, and collect the precipitate by centrifugation using anhydrous ethanol as a precipitation aid to obtain hydrophilic hydroxyapatite doped with strontium and europium ions.

[0015] Figure 1 TEM image of the hydrophilic hydroxyapatite doped with strontium and europium ions in Example 1. Figure 1 It can be seen that the hydrophilic hydroxyapatite doped with strontium and europium ions is 150-300 nm long and 10-15 nm wide, and is in the shape of nanorods with uniform size.

[0016] Figure 2 is the XRD pattern of the hydrophilic hydroxyapatite doped with strontium and europium ions in Example 1. Figure 2 It can be seen that the comparison with the hydroxyapatite standard card JCPDS no.74-0565 shows that the product is hydroxyapatite.

[0017] Figure 3 FT-IR images of the Sr and Eu co-doped hydroxyapatite before and after hydrophilic modification of Example 1. Figure 3 Visible, 3500~3000 cm -1 The stretching vibration peak of the hydrophilic -OH group appeared, indicating that the hydrophilic modification was successful. Example 2

[0018] This embodiment provides a hydrophilic hydroxyapatite doped with strontium and europium ions, and the preparation method thereof includes: (1) Under magnetic stirring, 1 mL of methyl oleate and 5 mL of methanol were mixed to obtain a precursor solution; 6.3 mL of 0.28 M Ca(NO 3 ) 2 of aqueous solution, 0.35 mL of 0.28 M Sr(NO 3 ) 2 of aqueous solution and 0.35 mL of 0.28 M Eu(NO 3 ) 3 The aqueous solution was stirred for 10 min and 7 mL of 0.168 M Na 3 PO 4 The aqueous solution was stirred for 10 minutes to obtain a mixed solution A; the mixed solution A was placed in a polytetrafluoroethylene reactor, sealed, and reacted at 100° C. for 5 hours; the system after the reaction was cooled to room temperature, and the precipitate was collected by centrifugation; (2) Disperse 0.05 g of the precipitate in 100 mL of Tris-HCl buffer, add 0.2 g of tannic acid, stir for 8 h, and collect the precipitate by centrifugation using anhydrous ethanol as a precipitation aid to obtain hydrophilic hydroxyapatite doped with strontium and europium ions.

[0019] The performance of the hydrophilic hydroxyapatite doped with strontium and europium ions in this embodiment is basically consistent with that in embodiment 1. Example 3

[0020] This embodiment provides a hydrophilic hydroxyapatite doped with strontium and europium ions, and the preparation method thereof includes: (1) Under magnetic stirring, 1 mL of methyl oleate and 7 mL of methanol were mixed to obtain a precursor solution; 4.9 mL of 0.28 M Ca(NO 3 ) 2 of aqueous solution, 1.05 mL of 0.28 M Sr(NO 3 ) 2 of aqueous solution and 1.05 mL of 0.28 M Eu(NO 3 )3 The aqueous solution was stirred for 10 min and 7 mL of 0.168 M Na 3 PO 4 The aqueous solution was stirred for 10 minutes to obtain a mixed solution A; the mixed solution A was placed in a polytetrafluoroethylene reactor, sealed, and reacted at 200° C. for 15 hours; the system after the reaction was cooled to room temperature, and the precipitate was collected by centrifugation; (2) Disperse 0.05 g of the precipitate in 100 mL of Tris-HCl buffer, add 0.4 g of tannic acid, stir for 12 h, and collect the precipitate by centrifugation with anhydrous ethanol to obtain hydrophilic hydroxyapatite doped with strontium and europium ions.

[0021] The performance of the hydrophilic hydroxyapatite doped with strontium and europium ions in this embodiment is basically consistent with that in embodiment 1. Example 4

[0022] This embodiment provides a solution of chondroitin sulfate CS-ADH containing a grafted hydrazide group, and the preparation method thereof comprises: (2) Dissolve 1 g of chondroitin sulfate CS in 100 mL of deionized water under stirring, adjust the pH to 5-6 with 1 M hydrochloric acid solution, add 1 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 2 g of N-hydroxysuccinimide, and stir for 10 min to activate the carboxyl groups; (2) Add 0.67 g of adipic acid dihydrazide to the system after activation of the carboxyl group, and stir at room temperature for 6 h; (3) The reaction system was transferred to a dialysis bag with a cutoff of 3500Da, and dialyzed with deionized water for 3 days. The deionized water was replaced every day during the dialysis process. The dialyzed system was freeze-dried to obtain chondroitin sulfate CS-ADH grafted with hydrazide groups; (4) Dissolve 0.05 g of CS-ADH in 1 mL of PBS to obtain a solution of chondroitin sulfate CS-ADH containing grafted hydrazide groups.

[0023] Figure 4 FT-IR images of chondroitin sulfate before and after modification in Example 4. Figure 4 Visible, 1635 cm -1 A characteristic absorption peak belonging to the amino group appears at , indicating that the grafting of the hydrazide group is successful.

[0024] Figure 5 Example 4 1H-NMR graph of chondroitin sulfate before and after modification. Figure 5 It can be seen that compared with CS, characteristic absorption peaks appeared at 1.5 and 2.2 ppm in the CS-ADH curve, indicating that the grafting of hydrazide groups was successful. Example 5

[0025] This embodiment provides a solution of chondroitin sulfate CS-ADH containing a grafted hydrazide group, and the preparation method thereof comprises: (1) Under stirring conditions, 10 g of chondroitin sulfate CS was dissolved in 100 mL of deionized water, and the pH of the solution was adjusted to 5-6 with 1 M hydrochloric acid solution. 20 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 10 g of N-hydroxysuccinimide were added and stirred for 30 min to activate the carboxyl groups. (2) Add 20 g of adipic acid dihydrazide to the system after activation of the carboxyl group, and stir at room temperature to react for 15 hours; (3) The reaction system was transferred to a dialysis bag with a cutoff of 3500Da, and dialyzed with deionized water for 5 days. The deionized water was replaced every day during the dialysis process. The dialyzed system was freeze-dried to obtain chondroitin sulfate grafted with hydrazide groups CS-ADH; the performance of the chondroitin sulfate grafted with hydrazide groups in this example was basically the same as that in Example 4; (4) 0.2 g of CS-ADH was dissolved in 1 mL of PBS to obtain a solution of chondroitin sulfate CS-ADH containing grafted hydrazide groups. Example 6

[0026] This embodiment provides a solution of chondroitin sulfate CS-ADH containing a grafted hydrazide group, and the preparation method thereof comprises: (1) Dissolve 10 g of chondroitin sulfate CS in 500 mL of deionized water under stirring, adjust the pH of the solution to 5-6 with 1 M hydrochloric acid solution, add 15 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 15 g of N-hydroxysuccinimide, and stir for 50 min to activate the carboxyl groups; (2) Add 15 g of adipic acid dihydrazide to the system after activation of the carboxyl group, and stir at room temperature to react for 24 hours; (3) The system after the reaction was transferred to a dialysis bag with a cutoff of 3500Da, and dialyzed with deionized water for 4 days. The deionized water was replaced every day during the dialysis process. The dialyzed system was freeze-dried to obtain chondroitin sulfate CS-ADH grafted with hydrazide groups. The performance of the chondroitin sulfate grafted with hydrazide groups in this example was basically the same as that in Example 4. (4) 0.5 g of CS-ADH was dissolved in 1 mL of PBS to obtain a solution of chondroitin sulfate CS-ADH containing grafted hydrazide groups. Example 7

[0027] This embodiment provides a solution of oxidized hyaluronic acid OHP containing grafted phenylboronic acid groups, wherein the oxidized hyaluronic acid grafted with phenylboronic acid groups is obtained by first grafting 3-aminophenylboronic acid onto hyaluronic acid and then performing aldehyde modification, and the preparation method thereof comprises: (1) Under stirring conditions, 1 g of hyaluronic acid was dissolved in 100 mL of deionized water, and the pH was adjusted to 5-6 with a 1 M hydrochloric acid solution. 2 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 1 g of N-hydroxysuccinimide were added, and the mixture was stirred for 10 min to activate the carboxyl groups. 0.4 g of 3-aminophenylboronic acid was added to the system after the carboxyl groups were activated, and the mixture was stirred at room temperature for 6 h. The reaction system was transferred to a dialysis bag with a cutoff of 3500 Da, and dialyzed with deionized water for 3 days to obtain hyaluronic acid (HP) grafted with phenylboronic acid groups. (2) Under stirring conditions, 0.8 g of hyaluronic acid grafted with phenylboronic acid groups was dissolved in 80 mL of deionized water, and 0.8 g of sodium periodate was added. The reaction was stirred for 1 h in the dark. 5 mL of ethylene glycol was added to the reaction system, and the reaction was terminated by stirring for 1 h. The terminated reaction system was transferred to a dialysis bag with a cutoff of 3500 Da, and dialyzed with deionized water for 3 days. The deionized water was replaced every day during the dialysis process. The dialyzed system was freeze-dried to obtain oxidized hyaluronic acid (OHP) grafted with phenylboronic acid groups. (3) Dissolve 0.05 g of OHP in 1 mL of PBS to obtain a solution of hyaluronic acid OHP containing grafted phenylboronic acid groups.

[0028] Figure 6 FT-IR images of Example 7 before and after hyaluronic acid modification. Figure 6 It can be seen that compared with HA, the 1558 cm -1 The characteristic absorption peak at 1645 cm-1 in the OHP curve is attributed to the phenylboronic acid group, indicating that the grafting of the phenylboronic acid group is successful, indicating that the modification of HP is successful. -1 The characteristic peaks belonging to the aldehyde group appeared, indicating that the modification of OHP was successful.

[0029] Figure 7 1H-NMR diagram of hyaluronic acid before and after modification in Example 7. Figure 7 It can be seen that compared with HA, a new characteristic peak appears at 7.4~7.8 ppm in the HP curve, indicating that the modification of HP is successful; compared with HP, a new characteristic peak appears at 4.9~5.0 ppm in the OHP curve, indicating that the modification of OHP is successful. Example 8

[0030] This embodiment provides a solution of oxidized hyaluronic acid OHP containing grafted phenylboronic acid groups, and the preparation method thereof comprises: (1) Under stirring conditions, 8 g of hyaluronic acid was dissolved in 800 mL of deionized water, and the pH was adjusted to 5-6 with a 1 M hydrochloric acid solution. 16 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 16 g of N-hydroxysuccinimide were added, and the mixture was stirred for 30 min to activate the carboxyl groups. 5 g of 3-aminophenylboronic acid was added to the system after the carboxyl groups were activated, and the mixture was stirred at room temperature for 15 h. The reaction system was transferred to a dialysis bag with a cutoff of 3500 Da, and dialyzed with deionized water for 5 days to obtain hyaluronic acid (HP) grafted with phenylboronic acid groups. (2) Under stirring conditions, 8 g of hyaluronic acid grafted with phenylboronic acid groups was dissolved in 800 mL of deionized water, and 24 g of sodium periodate was added. The mixture was stirred in the dark for 3 h. 10 mL of ethylene glycol was added to the reaction system, and the reaction was terminated by stirring for 3 h. The terminated reaction system was transferred to a dialysis bag with a cutoff of 3500 Da, and dialyzed with deionized water for 5 days. The deionized water was replaced every day during the dialysis process. The dialyzed system was freeze-dried to obtain oxidized hyaluronic acid (OHP) grafted with phenylboronic acid groups. (3) Dissolve 0.2 g of OHP in 1 mL of PBS to obtain a solution of hyaluronic acid OHP containing grafted phenylboronic acid groups. Example 9

[0031] This embodiment provides a solution of oxidized hyaluronic acid OHP containing grafted phenylboronic acid groups, and the preparation method thereof comprises: (1) Under stirring conditions, 10 g of hyaluronic acid was dissolved in 500 mL of deionized water, and the pH was adjusted to 5-6 with a 1 M hydrochloric acid solution. 15 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 15 g of N-hydroxysuccinimide were added, and the mixture was stirred for 50 min to activate the carboxyl groups. 7 g of 3-aminophenylboronic acid was added to the system after the carboxyl groups were activated, and the mixture was stirred at room temperature for 24 h. The reaction system was transferred to a dialysis bag with a cutoff of 3500 Da, and dialyzed with deionized water for 4 days to obtain hyaluronic acid (HP) grafted with phenylboronic acid groups. (2) Under stirring conditions, 2 g of hyaluronic acid grafted with phenylboronic acid groups was dissolved in 80 mL of deionized water, 4 g of sodium periodate was added, and the reaction was stirred for 5 h in the dark; 8 mL of ethylene glycol was added to the reaction system, and the reaction was terminated by stirring for 5 h; the terminated reaction system was transferred to a dialysis bag with a cutoff of 3500 Da, and dialyzed with deionized water for 4 days. The deionized water was replaced every day during the dialysis process, and the dialyzed system was freeze-dried to obtain oxidized hyaluronic acid (OHP) grafted with phenylboronic acid groups; (3) Dissolve 0.5 g of OHP in 1 mL of PBS to obtain a solution of hyaluronic acid OHP containing grafted phenylboronic acid groups. Example 10

[0032] This embodiment provides an injectable hydrogel, the preparation method of which includes: 0.05 g of hydrophilic hydroxyapatite doped with strontium and europium ions, 0.33 mL of a 5% solution of chondroitin sulfate grafted with hydrazide groups, 0.33 mL of a 5% solution of oxidized hyaluronic acid grafted with phenylboronic acid groups, and 0.33 mL of a 5% solution of recombinant collagen were mixed and stirred to obtain an injectable nanocomposite hydrogel.

[0033] Injectable hydrogel performance evaluation: Figure 8 The figure is a schematic diagram of the injectable performance of the injectable hydrogel described in Example 10. The injectable hydrogel is loaded into a syringe and injected into the target site. The result shows that the hydrogel of the present invention can be injected.

[0034] Cytological experiments The injectable hydrogel described in Example 10 was used as a research object to investigate its effect of promoting the growth of normal cells (chondrocytes), specifically including: (1) Preparation of DMEM extract of injectable hydrogel The injectable hydrogel is freeze-dried, sterilized by Co-60 irradiation, and immersed in DMEM complete culture medium at a concentration of 0.1 g / mL for 3 days (37° C.) to obtain a hydrogel extract, which is filtered with a filter membrane before use to obtain a DMEM extract of the injectable hydrogel; (2) Determination of the toxicity of injectable hydrogels to chondrocytes: ①Cell layout: 1×10 4 The cell dispersion was placed in a well plate with a cell density of 100 μL per well of the 96-well plate. The cells were placed in an incubator (37°C, 5% CO 2 ) Culture for 24h; ② Cytotoxicity detection: Take out the 96-well plates to which the chondrocytes have attached, replace the culture medium with the DMEM extract of the injectable hydrogel in step 1, and place them in an incubator (37°C, 5% CO 2 ) were cultured. At 24 and 48 h, 50 μL of MTT was added to each well, and the incubation was continued for 2-4 h. Then, all the liquid in the wells was removed, 150 μL of DMSO was added to each well, and the absorbance (OD) value corresponding to each well was detected at 490 nm using a microplate reader, and the cell survival rate was calculated based on the OD value. The blank group was cultured with cells using DMEM complete culture medium.

[0035] The results of the hydrogel effect experiment on chondrocytes are as follows Fig. 9 As shown. Fig. 9It can be seen that after culturing for 24 hours and 48 hours, the survival rate of chondrocytes was higher than 100%, indicating that the hydrogel had no cytotoxicity to chondrocytes and had the effect of promoting the proliferation of cartilage and accelerating the repair of cartilage defects. Embodiment 11

[0036] This embodiment provides an injectable hydrogel, the preparation method of which includes: 0.5 g of hydrophilic hydroxyapatite doped with strontium and europium ions, 0.3 mL of 30% chondroitin sulfate solution grafted with hydrazide groups, 0.5 mL of 30% oxidized hyaluronic acid solution grafted with phenylboronic acid groups, and 0.2 mL of 30% recombinant collagen solution were mixed and stirred to obtain an injectable nanocomposite hydrogel.

[0037] The performance of the injectable hydrogel in this example is basically consistent with that in Example 10. Example 12

[0038] 1 g of hydrophilic hydroxyapatite doped with strontium and europium ions, 0.3125 mL of a 30% solution of chondroitin sulfate grafted with hydrazide groups, 0.625 mL of a 30% solution of oxidized hyaluronic acid grafted with phenylboronic acid groups, and 0.0625 mL of a 30% solution of recombinant collagen were mixed and stirred to obtain an injectable nanocomposite hydrogel.

[0039] The performance of the injectable hydrogel in this example is basically consistent with that in Example 10.

[0040] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural change made to the above embodiments according to the technical essence of the invention still fall within the protection scope of the technical solution of the present invention. This research is funded by the National Key R&D Program (Design, Construction and Pathway Assembly of Key Enzyme Elements for Glycosaminoglycan Derivatives and Glycoprotein Synthesis, 2023YFA0914301).

Claims

1. A method for preparing an injectable nanocomposite hydrogel for relieving osteoarthritis, characterized in that The following steps are involved: (1) preparing hydrophilic hydroxyapatite doped with strontium and europium ions, specifically comprising: dissolving aqueous solutions of Ca(NO3)2, Sr(NO3)2, Eu(NO3)3 and aqueous solutions of soluble phosphates in a methanol solution of methyl oleate in sequence to obtain a mixed solution, reacting the mixed solution at 100-200°C in a closed reactor for 5-15 hours, and collecting the precipitate; dispersing the precipitate in a Tris-HCl buffer, adding tannic acid, stirring thoroughly, and collecting the precipitate to obtain hydrophilic hydroxyapatite doped with strontium and europium ions; (2) preparing a solution of chondroitin sulfate grafted with hydrazide groups, specifically comprising: dissolving 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide in an aqueous solution of chondroitin sulfate at a pH of 5 to 6 and stirring the solution to activate the carboxyl groups; adding adipic acid dihydrazide to the system after the carboxyl groups are activated for a sufficient reaction; transferring the system after the reaction to dialysis and freeze-drying to obtain chondroitin sulfate grafted with hydrazide groups; dissolving the chondroitin sulfate grafted with hydrazide groups in a PBS buffer solution to obtain a solution of chondroitin sulfate containing grafted hydrazide groups; (3) preparing a hyaluronic acid solution grafted with phenylboronic acid groups, specifically comprising: placing 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide in an aqueous solution of hyaluronic acid at a pH of 5 to 6 and stirring thoroughly to activate the carboxyl groups; adding 3-aminophenylboronic acid to the system after the carboxyl groups are activated to react thoroughly; transferring the system after the reaction to dialysis, and freeze-drying to obtain hyaluronic acid grafted with phenylboronic acid groups; dissolving the oxidized hyaluronic acid grafted with phenylboronic acid groups in deionized water to obtain an aqueous solution of hyaluronic acid containing grafted with phenylboronic acid groups; (4) preparing an oxidized hyaluronic acid solution grafted with phenylboronic acid groups, specifically comprising: dissolving sodium periodate in an aqueous solution of hyaluronic acid grafted with phenylboronic acid groups, adding ethylene glycol after sufficient reaction in a dark environment, and stirring to terminate the reaction; dialyzing the system after the termination of the reaction, and freeze-drying to obtain an oxidized hyaluronic acid grafted with phenylboronic acid groups; dissolving the oxidized hyaluronic acid grafted with phenylboronic acid groups in a PBS buffer solution to obtain an oxidized hyaluronic acid solution containing grafted with phenylboronic acid groups; (5) Preparing an injectable nanocomposite hydrogel, specifically comprising: uniformly blending the hydrophilic hydroxyapatite doped with strontium and europium ions in step (1), the chondroitin sulfate solution grafted with hydrazide groups in step (2), the oxidized hyaluronic acid solution grafted with phenylboronic acid groups in step (4), and the recombinant collagen solution to obtain the injectable nanocomposite hydrogel.

2. The method for preparing the injectable nanocomposite hydrogel according to claim 1, characterized in that: In step (1), in the methanol solution of methyl oleate, the volume of methanol is 3 to 7 times the volume of methyl oleate; the molar ratio of (Ca+Sr+Eu) / P is 1.67, and the molar ratio of Sr / (Ca+Sr+Eu) is 0.05 to 0.5; the soluble phosphate is selected from Na2HPO4, Na3PO4·12H2O, NaH2PO4, KH2PO4 or K2HPO4; the molar ratio of Eu / (Ca+Sr+Eu) is 0.05 to 0.5; the volume of cyclohexane is 10 to 100 times the mass of the precipitate; and the mass of tannic acid is 3 to 6 times the mass of the precipitate.

3. The method for preparing the injectable nanocomposite hydrogel according to claim 1, characterized in that: In step (2), the mass of the 1-ethyl-(3-dimethylaminopropyl)carbodiimide is 1 to 2 times the mass of chondroitin sulfate, the mass of the N-hydroxysuccinimide is 1 to 2 times the mass of chondroitin sulfate; and the mass of the adipic acid dihydrazide is 0.67 to 2 times the mass of chondroitin sulfate.

4. The method for preparing the injectable nanocomposite hydrogel according to claim 1, characterized in that: In step (3), the mass of the 1-ethyl-(3-dimethylaminopropyl)carbodiimide is 1 to 2 times the mass of hyaluronic acid, the mass of the N-hydroxysuccinimide is 1 to 2 times the mass of hyaluronic acid, and the mass of the 3-aminophenylboronic acid is 0.2 to 1 times the mass of hyaluronic acid.

5. The method for preparing the injectable nanocomposite hydrogel according to claim 1, characterized in that: In step (4), the mass of the sodium periodate is 1 to 3 times the mass of the hyaluronic acid grafted with phenylboronic acid groups; and the volume of the ethylene glycol is 1.25 to 6.25 times the mass of the hyaluronic acid grafted with phenylboronic acid groups.

6. The method for preparing the injectable nanocomposite hydrogel according to claim 1, characterized in that: In step (5), the concentration of hydrophilic hydroxyapatite doped with strontium and europium ions is 0.05-1 g / mL, the concentration of the chondroitin sulfate solution grafted with hydrazide groups is 5-50%, the concentration of the oxidized hyaluronic acid solution grafted with phenylboronic acid groups is 5-50%, and the concentration of the recombinant collagen solution is 5-50%; the volume ratio of the chondroitin sulfate solution grafted with hydrazide groups, the oxidized hyaluronic acid solution grafted with phenylboronic acid groups, and the recombinant collagen solution is (1-5):(1-10):(1-5).

7. The injectable nanocomposite hydrogel prepared by the method according to any one of claims 1 to 6.

8. Use of the injectable nanocomposite hydrogel according to claim 7 in the preparation of medicines for treating and relieving osteoarthritis.

Citation Information

Patent Citations

  • Novel injectable hydrogel for bone defect repair and preparation method thereof

    CN112999427A

  • Schiff base hydrogel material with side chain grafted with phenylboronic acid and active oxygen eliminating function and preparation method of Schiff base hydrogel material

    CN113730577A

  • Structural protein / hyaluronic acid composite micro-nano particle, particle hydrogel material and application

    CN115521627A

  • Temperature-sensitive injectable chitosan / silk fibroin / hydrotalcite composite hydrogel as well as preparation method and application thereof

    CN115845148A

  • Novel injectable hydrogel for bone joint treatment and preparation method thereof

    CN116421550A

Cited By

  • Cartilage repair hydrogel material and preparation method thereof

    CN119405890A

  • Cartilage repair hydrogel material and preparation method thereof

    CN119405890B

  • Temperature-sensitive controlled-release hydrogel composite material for osteoarthritis repair and preparation method of temperature-sensitive controlled-release hydrogel composite material

    CN119970627A

  • Hydrogel component for transferring exosome and preparation method thereof

    CN120204470A

  • Nano-composite hydrogel for diabetic bone repair and preparation method of nano-composite hydrogel

    CN121846366A